ORGANIZATION OF CULTURAL AND COGNITIVE TOURISM. CURRENT STATE AND DEVELOPMENT TRENDS IN UKRAINE - PANKIV, Natalia; SAGAYDAK, Viktiriia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The history of the origin of cultural and cognitive tourism, its concept and essence, as well as the general requirements for the development of cultural and cognitive tours are analyzed. An analysis of the development of cultural and cognitive tourism in the Ukrainian market and assessment of the cultural heritage of Ukraine. Trends in the development of cultural tourism in the Lviv region, in particular, in cities as important centers of cultural and cognitive tourism and attracting tourism innovations on the example of the city of Lviv. Trends in the development of cultural and cognitive tourism and the use of world experience for the development of historical and cultural cognitive tourism in Ukraine are studied. Practical recommendations on ways to improve the use of cultural and cognitive resources of the regions are given. It is established that Ukraine has a large number of unique monuments of history and culture, and therefore has great potential for the development of inbound and domestic cultural and cognitive tourism. Unfortunately, some of them were destroyed as a result of a full-scale invasion of the territory of Ukraine by the troops of the Russian Federation. racists continue war crimes against Ukrainian heritage, trying to erase Ukrainian history and identity. Destroying Ukrainian culture is one of their strategic goals in this war! Already in Ukraine, more than 350 cases of destruction of cultural heritage sites by the Russian occupation forces have been recorded. It is very difficult to protect them during the war because we are dealing with especially cynical barbarians, for whom our cultural monuments are one of the most important targets on the way to the realization of their dream - the destruction of the Ukrainian nation! But we will not allow it! The struggle continues! We must preserve the history and culture of Ukraine for our descendants!